2014
DOI: 10.1590/0034-737x201461050004
|View full text |Cite
|
Sign up to set email alerts
|

Influência da densidade do solo no desenvolvimento inicial do pinhão-manso cultivado em Latossolo Vermelho eutroférrico

Abstract: Este trabalho teve por objetivo avaliar a influência da densidade do solo no desenvolvimento inicial da cultura do pinhão-manso. O experimento foi realizado em vasos de 10,6 dm³, em casa de vegetação. O solo utilizado foi o Latossolo Vermelho eutroférrico de textura argilosa, coletado em Marechal Cândido Rondon - PR. O delineamento experimental utilizado foi o de blocos casualizados, composto por cinco níveis de densidade do solo (1,08; 1,22; 1,36; 1,50 e 1,64 kg dm-3), com quatro repetições. Após 120 dias da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
2
7
0
6
Order By: Relevance
“…Soil compaction is characterized by changes in the physical properties of a soil due to a specific management practice in which the soil is subjected to a specific pressure, which reduces the soil's volume and increases its penetration resistance and density (Oliveira et al, 2010;Ohland et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soil compaction is characterized by changes in the physical properties of a soil due to a specific management practice in which the soil is subjected to a specific pressure, which reduces the soil's volume and increases its penetration resistance and density (Oliveira et al, 2010;Ohland et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Borges et al (1986), evaluating the effect of soil compaction in the initial growth of three species of eucalyptus, observed that for the species tested, the negative regression coefficient showed that even small, there was a decrease in the shoot dry mass of the seedlings. Ohland et al (2014), also report a linear decreasing trend of the variable height for the species Jatropha curcas L., being observed a reduction in plant height of approximately 25% to the highest level of compression tested (1.64 kg dm -3 ), when compared with lower density (1.08 kg dm -3…”
Section: Resultsmentioning
confidence: 66%
“…According to Neves et al (2005), it is necessary to adequate number of channels that are large enough to allow the roots may penetrate vertically in the ground and develop. Ohland et al (2014) evaluated the influence of soil density in the initial development of J. curcas L. and reported that densities between 1.50 and 1.64 kg dm -3…”
Section: Resultsmentioning
confidence: 99%
“…Rondonópolis -MT, 2014. CV -coefficient of variation Ohland et al (2014), also observed that the increase in density levels in Oxisol, influenced the number of safflower and jatropha leaves, with quadratic effect as a function of soil density levels, up to a density of 1.26 Mg m -3 .…”
Section: Number Of Leavesmentioning
confidence: 83%